Developing Infographics as Wellness Education Media and Local Product Internationalization - Jotika Purnama Yuda; Desi Wulandari; Yanuarria Kukuh Perwira; Karlina Denistia; Intan Mustika Sari; Agus Dwi Priyanto (Mudra Jurnal Seni Budaya, 2023)
Mental health and the concept of wellness have not been widely known by the Indonesian people, especially the millennial generation and Gen Z. Rumah Atsiri Indonesia (RAI) is an organization engaged in the creative industry sector that promotes wellness as their main theme. In its business, RAI strives to educate the public about the concept of wellness and introduce the benefits of essential oils as their product. To support these activities, attractive and effective means of communication and education are needed. Responding to this problem, the English for Creative Industry Research Group of the English Diploma 3 Study Program, Vocational School (SV), Universitas Sebelas Maret conducted a community service activity by developing infographics as educational media about the concept of wellness and essential oil products. The infographic was created using the ADDIE design method. Evaluation was done by distributing the developed infographics to get input from 129 respondents. The evaluation results show that the developed infographic media is effective and attractive in delivering educational content about wellness and essential oil product internationalization. Visual displays and dissemination media that are tailored to the target audience have succeeded in improving respondents' understanding of the concept of wellness and inspiring them to implement it, as well as to participate in sharing the created infographics.